Patient- and relative-activated critical care outreach: a 7-year service review. (24th January 2019) - Odell, Mandy
Abstract : Five years following the introduction of a whole-hospital, 24-hour critical care outreach (CCO) service, an additional service was introduced that enabled patients and their families to directly call the CCO team if they had concerns that were not being acknowledged by the patient's clinical team. The aim of this review was to report on 7 years of patient and family referrals using quantitative and free text data extracted from the CCO referral database. Information on demographics, frequency, nature and reason for the referrals have been reported that highlight the feasibility of such a service, and the potential to prevent patient deterioration. By tapping into the rich source of information from family concerns, future hospital services could be designed that could not only have an impact on patient outcome, but also positively influence the quality of the patient experience.